2001
DOI: 10.1123/apaq.18.4.434
|View full text |Cite
|
Sign up to set email alerts
|

Scholarly Productivity in Adapted Physical Activity Pedagogy: A Bibliometric Analysis

Abstract: The purpose was to determine whether publications pertaining to adapted physical activity (APA) pedagogy in the core serials from 1988 to 1998 adhere to library science laws. A bibliometric analysis was conducted on 770 articles in 259 serials selected from 4,130 serials initially identified in four databases (Article First, ERIC, Medline, Sport Discus). Results indicated that 1,720 authors have constructed the early APA pedagogy literature. Of these, only 11 contributed four or more articles. The scatter of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Most of them made bibliometric studies on specific sports or topics, such as judo, rugby, physical activity and aging, anabolic steroids and drug abuse, rehabilitation, disability sport, adapted physical activity, cardiology and sport and sport psychology. [2][3][4][5][6][7][8][9][10] Others just focus on one journal, such as International Review for the Sociology of Sport, 11 Journal of Orthopaedic & Sports Physical Therapy, 12 Journal of Rehabilitation and Medicine, 13 14 or on several journals, normally relate to sub-disciplines in sport sciences, such as physical and rehabilitation medicine, rehabilitation, sport management and marketing or sports economics. [15][16][17][18] Sometimes they also focus on sport sciences in specific country or region, such as Spain, Iran, Croatia and South America.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them made bibliometric studies on specific sports or topics, such as judo, rugby, physical activity and aging, anabolic steroids and drug abuse, rehabilitation, disability sport, adapted physical activity, cardiology and sport and sport psychology. [2][3][4][5][6][7][8][9][10] Others just focus on one journal, such as International Review for the Sociology of Sport, 11 Journal of Orthopaedic & Sports Physical Therapy, 12 Journal of Rehabilitation and Medicine, 13 14 or on several journals, normally relate to sub-disciplines in sport sciences, such as physical and rehabilitation medicine, rehabilitation, sport management and marketing or sports economics. [15][16][17][18] Sometimes they also focus on sport sciences in specific country or region, such as Spain, Iran, Croatia and South America.…”
Section: Introductionmentioning
confidence: 99%
“…The generalization of these findings may be questioned, since IR in APA-related topics may appear in many different journals based on scientific discipline (e.g., in exercise physiology, biomechanics, special education, or sport psychology) or target population (e.g., Developmental Medicine and Child Neurology, Journal of Intellectual Disability Research, Spinal Cord, Stroke). However, large-scale documentary analyses performed about a decade ago have indicated that APAQ is the most popular source for publication of APA related scholarly articles (O'Connor, French, Sherrill, & Babcock, 2001;Porretta, Kozub, & Lisboa, 2000;Reid & Prupas, 1998). Therefore, it seems justifiable to assume that APAQ represents trends in APA data-based research.…”
Section: Historical Perspectives Of Ebp/ebr In Apamentioning
confidence: 99%
“…In addition a few bibliometric studies on sport education were also found (O'Connor et al, 2001;Barczyński, 2013;Završnik et al, 2015). A few years back O'Connor et al (2001) in their study analysed if adapted physical activity pedagogy adhere to information science laws (i.e. Bradford and Price laws).…”
Section: Reviewmentioning
confidence: 99%
“…Previously researchers already used various bibliometric studies to investigate information sources in sports medicine for example analysing the history of the particular journal (Fritz et al, 2011), top cited articles in orthopaedic surgery (Lefaivre et al, 2011) or research literature production on leisure time sports injuries (Vitzthum et al, 2010). In addition a few bibliometric studies on sport education were also found (O'Connor et al, 2001;Barczyński, 2013;Završnik et al, 2015). A few years back O'Connor et al (2001) in their study analysed if adapted physical activity pedagogy adhere to information science laws (i.e.…”
Section: Reviewmentioning
confidence: 99%